2019
DOI: 10.1016/j.jcsr.2018.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of material nonlinearity on the global analysis and stability of stainless steel frames

Abstract: In structural frames, second order effects refer to the internal forces and moments that arise as a result of deformations under load (i.e. geometrical nonlinearity). EN 1993-1-1 states that global second order effects may be neglected if the critical load factor of the frame cr is greater than 10 for an elastic analysis, or greater than 15 when a plastic global analysis is used. No specific guidance is provided in EN 1993-1-4 for the design of stainless steel frames, for which the nonlinear stress-strain beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 13 publications
2
70
0
Order By: Relevance
“…A local imperfection amplitude of ωl = c / 200 was assumed, as recommended in EN 1993-1-5:2006(CEN 2006c) and successfully employed in several previous numerical studies e.g. and Walport et al (2019). Note that the measured local imperfection amplitudes (Ma et al 2016;Meng and Gardner 2019b) for the considered SHS and RHS profiles were, on average, slightly smaller than the value of c / 200 recommended in EN 1993-1-5:2006(CEN, 2006c, and thus, slightly conservative resistance predictions from the FE models were anticipated.…”
Section: Validationmentioning
confidence: 99%
“…A local imperfection amplitude of ωl = c / 200 was assumed, as recommended in EN 1993-1-5:2006(CEN 2006c) and successfully employed in several previous numerical studies e.g. and Walport et al (2019). Note that the measured local imperfection amplitudes (Ma et al 2016;Meng and Gardner 2019b) for the considered SHS and RHS profiles were, on average, slightly smaller than the value of c / 200 recommended in EN 1993-1-5:2006(CEN, 2006c, and thus, slightly conservative resistance predictions from the FE models were anticipated.…”
Section: Validationmentioning
confidence: 99%
“…Material nonlinearity also affects the behaviour of the stainless steel structures at the frame level, but no explicit guidance on the treatment of material nonlinearity in global analyses is currently given in EN 1993-1-4. In the absence of guidance, an elastic analysis may be assumed to be acceptable for stainless steel frames, though recent research [78] has shown that this is not necessarily the case. The gradual degradation of material stiffness was shown in some instances to significantly affect the characteristics of the structural system and the subsequent distribution of internal forces and moments.…”
Section: Materials Nonlinearity At Frame Levelmentioning
confidence: 99%
“…If material nonlinearity is considered in the global analysis of a frame, greater deformations result due to the loss of material stiffness; if plasticity is ignored, peak moments are typically underpredicted. It was therefore recommended [78] that plastic analysis (employing the rounded material stress-strain response described in Section 2)…”
Section: Materials Nonlinearity At Frame Levelmentioning
confidence: 99%
“…As discussed in Walport et al [17], for elastic analysis, the amplification factor kamp is equivalent to the ratio of internal forces from a second (GNA) to a first order (LA) analysis (MGNA/MLA) at any point in the frame. However, for plastic analysis, due to the redistribution of the internal forces and moments following material nonlinearity, kamp must be calculated by determining the magnitude of the amplification of the horizontal loading in a first order analysis (MNA+ kamp) required to align the sway deflections to those in a second order analysis (GMNA) at a given applied load factor, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As presented in Walport et al [17] for stainless steel, the influence of plasticity on the sway stiffness of frames may be considered by defining a modified elastic buckling load factor αcr,mod, as given by Eq. (4).…”
Section: Proposed Approachmentioning
confidence: 99%